Comparison of Rajasri birds with indigenous birds in performance and haemo biochemical parameters under scavenging system during summer season - SRINIVAS, GURRAM; SWATHI, B (The Indian Journal of Animal Sciences, 2018)
Performance and haemo-biochemical parameters of Rajasri and Indigenous birds of northern region of Telangana state were studied under scavenging system of rearing. The overall mean body weight was significantly (P≤0.05) higher in Rajasri birds than indigenous birds from 6th to 52nd weeks of age. The mean age at sexual maturity was recorded as 172 days in case of Rajasri birds and in indigenous chicken it was recorded as 219 days. The mean egg production and egg weights of Rajasri bird from 32 to 52 weeks of age were significantly (P≤0.05) higher than indigenous birds. There was significantly (P<0.05) higher fertility and hatchability percent noticed in indigenous fowl compared to Rajasri birds. There was no significant difference noticed in total protein, SGOT, SGPT, bilirubin, calcium, phosphorus and blood glucose however there was significant difference in Haemoglobin, PCV, MCH, MCHC and serum cholesterol at 21st week of age.